Polyozellin, a key constituent of the edible mushroom Polyozellus multiplex, attenuates glutamate-induced mouse hippocampal neuronal HT22 cell death. Issue 12 (23rd September 2015) - Yang, Eun-Ju; Song, Kyung-Sik
Abstract : Polyozellin, a key constituent of Polyozellus multiplex, was applied to glutamate-treated HT22 cells to evaluate its neuroprotective mechanisms. Abstract : Polyozellus multiplex (PM), a Korean edible mushroom, has biological activities such as chemoprevention of stomach cancer, inhibition of lipid peroxidation, and reduction of prolyl endopeptidase activity. However, there are little reports on the protective effects of PM or its constituents against glutamate-induced mouse hippocampal neuronal cell (HT22) death. In this study, polyozellin (PZ), a key constituent of PM, was applied to glutamate-treated HT22 cells to evaluate its neuroprotective mechanisms. PZ (25 μM) dramatically increased the HT22 cell viability when the cell death was induced by 5 mM glutamate for 12 h, which was mediated by inhibition of Ca 2+ influx, intracellular reactive oxygen species (ROS) production, and lipid peroxidation. PZ also regulated expression of Bid, Bcl-2, and apoptosis-inducing factor (AIF), as well as phosphorylation of mitogen-activated protein kinases (MAPKs). These data suggest that PM and its constituent PZ might be useful for prevention and treatment of neurodegenerative disorders.